Meningkatkan Keadilan Sosial Ekonomi melalui Implementasi Akhlaq dalam Hukum Islam: Sosial Ekonomi, Akhlaq dan Hukum Islam - Kusyana, Kusyana; Romlah, Romlah; Subandi, Subandi (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2024)
This research aims to explore the potential for enhancing socio-economic justice through the implementation of ethics in Islamic law. Using a qualitative approach, the study analyzes concepts of ethics and principles of Islamic law relevant to economic contexts. The findings indicate that principles such as justice, honesty, and social responsibility play a crucial role in creating a fairer and more inclusive economic system. The research also identifies several challenges in implementing ethics within Islamic legal practices, including societal misunderstanding and awareness gaps regarding these concepts, as well as complexities in adapting them to modern economic contexts. Therefore, collaborative efforts are necessary from various stakeholders, including governments, civil society, and the private sector, to address these challenges and promote the implementation of ethical principles in Islamic law in everyday economic life. The research underscores that implementing ethics in Islamic law holds significant potential for enhancing socio-economic justice. Identifying challenges in implementing ethical principles in Islamic law, including lack of awareness and understanding, implementation difficulties, regulatory challenges, and lack of stakeholder cooperation, underscores the complexity yet importance of enhancing socio-economic justice through the implementation of ethics in Islamic law. Keywords: socioeconomic justice, morality, Islamic law, inclusive, collaborative